DSL-driven Integration of OpenAPI based Web Services into DIME - Steffen, Bruno (Electronic Communications of the EASST, 2023)
Since nowadays the vast majority of web developers integrate third party web services into their web applications, communities formed to standardize the API landscape. This resulted in formats such as the OpenAPI Specification (OAS), GraphQL, RAML and many more. The communities further strengthen their efforts by providing tools that assist web developers when working with third party web services. However, these tools are typically aimed at traditional code environments. This paper discusses an approach to make use of these formats, primarily the OAS, to automatically integrate web services into the low-code development environment called DIME. This is done by mapping the machine readable OAS files to domain-specific languages that in turn generate code for the final DIME application.